Peluang dan Tantangan Pengembangan UMKM Pati Angkrik di Desa Triharjo, Kabupaten Kendal - Sa’id ‘Ali Asyhari; Novi Lieana Anggraeni; Hilda Fairuz Zain; Nahnu Robid Jiwandono (Lembaga Pengembangan Kinerja Dosen, 2024)
Opportunities and challenges faced in developing MSMEs definitely exist in the MSME development process. Pati Angkrik as a local tuber food offers significant potential opportunities in improving community welfare. Pati Angkrik, which belongs to the group of tubers, can be processed into various processed food and beverage products. And the challenges faced by Pati Angkrik MSMEs include limited raw materials, limited human resources, time requirements, and ineffective marketing access, making the development of Pati Angkrik MSMEs also experiencing obstacles. Triharjo Village, Gemuh District, Kendal Regency, has the Pati Angkrik micro and small and medium enterprise (MSME) as one of the community businesses in Triharjo Village. However, there are challenges and opportunities it faces. The aim of this service is to provide MSME development to the challenges and opportunities faced by Pati Angkrik MSME actors in Triharjo Village, so that they can help Angkrik starch MSME actors by replacing more modern packaging and designing packaging for Angkrik starch MSME products. This devotion uses method Participatory Action Research is a method of raising public awareness regarding potential and existing problems and encouraging community participation in change activities that will be implemented. This service has succeeded in providing development for pati angkrik MSMEs by changing product packaging to modern packaging and creating packaging designs, so that the development of pati angkrik MSMEs can benefit the angkrik starch MSMEs in Triharjo Village.